Development and implementation of policies for the management of psychosocial risks: exploring the role of stakeholders and the translation of policy into practice in Europe - Jain, Aditya Kailash (2011)
The key aim of this research is to evaluate the impact of policy level interventions for the management of psychosocial risks in Europe. This research is exploratory in nature and seeks to clarify the policy framework in relation to psychosocial risk management, identify key policy stakeholders, examine their perceptions and clarify their role in the policy making process. The research also evaluates the impact of selected policies by analysing their implementation and impact on action at the national and enterprise levels.